PENGEMBANGAN MODEL PELATIHAN ONLINE BERBASIS WEB UNTUK KEUNGGULAN BERSAING PADA PT INTELLISYS TRIPRATAMA - Thomas Ivantoro Prasetyo; Gintoro Gintoro (CommIT (Communication and Information Technology) Journal, 2010)
In order to face competition, PT Intellisys, as the service provided in web-based online training, is trying to serve every customer from wherever and whenever in a good quality service. It started with the analysis of competitior’s condition using Porter’s five competitive forces analysis, internal condition using SWOT analysis, and internal componay process using Value Chain analysis to conclude a suitable IT strategy for the company. It is then continued with Work-Centered analysis to produce the increasing of business process then designing web-based online training system model in doing evaluation to show good accommodation and training service from Intellisys to customers that could bring the company competitive advantages. The research result is a model design from web-based online training system that is cheap and flexible, easier to get wherever and whenever, and also innovative and easier-to-learn material.Keywords: e-learning, competitive advantages, information technology, training service provider, SCROM